A QUALITATIVE EXPLORATION OF HEURISTICS AND COGNITIVE BIASES IN AUDITOR JUDGEMENTS - Maradona, Agus Fredy (ACCOUNTABILITY, 2020)
Professional judgement is inherent in financial statement audits because various methods, techniques, or approaches prescribed in auditing standards do not provide auditors with detailed guidance or specific audit criteria. While auditors are expected to exercise their judgements based on careful reasoning, there is a possibility that they do not always follow such an approach and instead make their judgements using heuristics. This study aims to penetrate and reveal whether there are cognitive biases in the judgements of auditors and what heuristics lead to these biases. This study employs a qualitative research design and uses ethnomethodology as a research approach. Data were collected using in-depth semi-structured interviews with 15 auditors who were either partners, managers, seniors, or juniors at a public accounting firm. Using the heuristic-bias framework as a theoretical lens and based on an analysis involving data condensation, data display, and conclusion drawing and verification, this study identifies five types of biases that auditors can experience: jumping to conclusions, groupthink, representativeness, availability, and anchoring biases. The results of this study present practical implications for auditors, accounting professional associations, public accounting firms, and academic institutions. That is, the findings provide insights for formulating strategies aimed at raising auditors’ awareness about possible systematic errors, or biases, in professional judgements when auditors rely on heuristics as a simplifying judgement-making strategy.